AKIBAT HUKUM PELAKSANAAN ARISAN PRESPEKTIF PERJANJIAN DALAM HUKUM PERDATA - Munir, Munir; Sukirman, Sukirman; Gufran, Gufran (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
In the implementation of research related to the legal consequences of the implementation of arisan in the perspective of this agreement is conducted. The purpose of this study is to determine the legal consequences of the implementation of the perspective of the agreement in civil law. In this study uses a type of normative law research, with several approaches. The statue approach is an approach used by reviewing all relevant laws and regulations in accordance with the law dealt with, conceptually and historically. The results of this study show that one form of agreement in society in general is the agreement to conduct arisan activities. Arisan is very similar to savings. As a system to save money, but this activity is also intended for meeting activities that have an element of coercion because members are required to pay and come when the lottery will be held. As a result of the law, the relationship between the legal subject and other legal subjects of an agreement, contains the fulfillment of the rights and obligations of the parties by mutual agreement as a law for those who make it. That is the meaning of the essential agreement regulated in article 1338 of the Civil Code. And article 1320 of the Civil Code is also the basis of an agreement that is consensualism. However, article 1338 paragraph (1) and article 1320 of the Civil Code are not enough to be used as a standard in the implementation of arisan as a